(untitled) (Fiep Bulletin - online, 2025)
The study aimed to analyze the differences in climbing self-efficacy and its relationships between groups based on sex, age and BMI (kg/m²). This cross- sectional study involved 34 climbers of both sexes, over 18 years of age. The Perceived General Self-Efficacy Scale was applied. Student’s t-test for independent samples was used to compare the self-efficacy variable between groups categorized by sex (female and male), age (< 40 years and > 40 years) and BMI (< 24 kg/m² and > 24 kg/m²). In addition, analyses of variance (ANOVA) were performed to evaluate the relationship between the independent variables (sex, age and BMI) and the independent variable (self-efficacy). It was found that there was no significant difference between the groups (p> 0.05), showing only a small to medium effect size. It should be noted that regardless of the differences in means, both groups presented a high score (4.22±0.42) for self-efficacy (minimum 2.9 and maximum 5.0). Likewise, there was no interaction between the variables (p>0.05). There was a relationship only for age (p=0.049), where the multiple comparison confirms the difference between <40 years and >40 years (p=0.048), revealing that those in the age group over 40 years have higher self-efficacy values. Based on this, the participants presented a high score for self-efficacy, with no difference or interaction between groups. Only age showed a significant relationship, with higher self- efficacy values in people over 40 years.